Psichiatria e psicoterapia nei servizi pubblici. Un focus sull’attualità - Masini, Andrea (Il sogno della farfalla, 2024)
From 1978 to the present day, mental health services in Italy have progressively developed on a model of territorial care considered a unique example of proximity medicine. However, 46 years after Law No. 180/1978 and Law No. 833/1978 came into force, it seems useful to seriously question the limits of this reform. Five psychiatrists and a psychologist, with significant experience in public services, answered some questions and offered their perspective. In particular, the authors highlighted the critical issues encountered in their work, at a regulatory and practice level, as well as on a general theoretical and cultural level.